1950
DOI: 10.3181/00379727-75-18081
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Fragility and Vitamin'P'Protective Action Against Radiation

Abstract: 6CAPILLARY FRAGILITY AND VIT. 'P' PROTECTIVE ACTION pletely dispense with that gland.Summary. Pregnancy has been maintained in rats hypophysectomized on day 6 of their first pregnancy and injected daily subcutaneously for 6 days with placentae from rats: 12 majority of the test rats. One 12-day placenta plus 0.5 pg of estrone proved equally efficacious. Pregnancy was not maintained by similar treatment if the rats were also o6phorectomized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1951
1951
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Flavanones are biologically active and there has been considerable interest in their antioxidant and other properties that may contribute to suppress inflammation and hence modulate events involved in the initiation and progression of cancer and cardiovascular dysfunction. Early work focused on the ability of citrus flavanones to affect capillary function ( 1 3 ) . More recently, it has been demonstrated that flavanones can modulate cell-signalling pathways that have been implicated in cancer, atherosclerosis and other inflammatory diseases ( 4 8 ) .…”
mentioning
confidence: 99%
“…Flavanones are biologically active and there has been considerable interest in their antioxidant and other properties that may contribute to suppress inflammation and hence modulate events involved in the initiation and progression of cancer and cardiovascular dysfunction. Early work focused on the ability of citrus flavanones to affect capillary function ( 1 3 ) . More recently, it has been demonstrated that flavanones can modulate cell-signalling pathways that have been implicated in cancer, atherosclerosis and other inflammatory diseases ( 4 8 ) .…”
mentioning
confidence: 99%
“…Also, in the 1950s citrus polyphenols, at that time called 'vitamin P', were shown to affect capillary fragility in rabbit ears [73]. Nevertheless, the research on polyphenols improving microvascular function in different vascular beds and linking that to a (cardiovascular) benefit is still in his infancy, reflected by the fact that 50% of the eligible studies were published in the last decade (Tables 1-9).…”
Section: Resultsmentioning
confidence: 99%
“…Considerable work was done with the determination of capillary permeability by using chloroform wheals applied to the skin and simultaneous injections of trypan blue. This test pertaining rather to permeability changes than to increased capillary fragility has demonstrated a great variation in the response of experimental animals to the same flavonoid compound (11,12). More recently it was suggested that radiation injury to the capillary wall might serve as a basis for the estimation of vitamin "P" activity.…”
mentioning
confidence: 99%